Literasi Digital dan Keluarga: Dinamika Pembelajaran Siswa di SMP Negeri 12 Binjai - Nopita Silaban; Pintauli Silaban; Tri Indah Prasasti; Febri Simamora; Grace Tampubolon; Osmer Nadeak (Indo Publishing, 2025)
The development of digital technology has had a significant impact on education, including at the secondary school level. Students' use of gadgets serves not only as a means of entertainment but also as a learning medium that can support digital literacy skills. However, the use of gadgets often presents challenges, especially when students receive little supervision from teachers or parents. This article aims to analyze the influence of gadget use, digital literacy, and family background on the learning dynamics and character education of students at SMP Negeri 12 Binjai. This study uses a descriptive qualitative approach with in-depth interviews. The main informant is Mrs. Juni, a Mathematics teacher and Vice Principal for Student Affairs, who plays a strategic role in student guidance and supervision. The results show that gadgets are not completely banned at school, but their use is regulated through coordination with teachers and the Guidance and Counseling Department. Digital literacy tends to be more attractive to students than library-based literacy, resulting in less than optimal library use. In addition, family background, especially for students from broken homes, influences their motivation, discipline, and character. These findings underscore the importance of synergy between technology utilization, literacy strengthening, and the role of families in achieving effective learning while simultaneously shaping student character in accordance with the Pancasila student profile.